Un projet parental à l’épreuve de l’infécondité à Hanoi (Vietnam) : des difficultés aux stratégies des couples pour avoir un enfant - Laurence Charton; Thi Van Nguyen (Genre, Sexualité et Société)
In Vietnam, the extended family plays an important social role: in particular, it regulates the behaviour of its members through the hierarchy of generations and the role and expectations attributed to each of them. In this societal and family model, marriage is an important step, as is the arrival of children. Nowadays, however, many Vietnamese couples say they have difficulties conceiving a child. Based on semi-structured interviews conducted in Hanoi in the spring of 2016 with ten married couples (men and women being interviewed separately), two married women and two divorced women who have no children, this article allows us to identify, through a processual approach of the infertility experience, the extent of social and family reproductive pressure that couples face. By showing the socio-emotional consequences of childlessness, it also highlights the gender oppression and intergenerational power relationships that are mainly experienced by childless